2017
DOI: 10.1080/24750573.2017.1385210
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume level in patients with generalized anxiety disorder

Abstract: OBJECTIVE: Generalized anxiety disorder (GAD) is characterized by persistent and chronic anxiety state. Stressful life events and anxiety usually cause an increase in platelet volume and activity through various mechanisms. Mean platelet volume (MPV), which is indicative of platelet size, is accepted as an indication of platelet activity. METHOD: In this first retrospective cohort study about MPV among GAD patients, we compared complete blood count especially in terms of platelet count (PLT), platelet distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
1
26
1
Order By: Relevance
“…[4][5][6][7]18 In addition, MPV has poor diagnostic value in patients with generalized anxiety disorder. 8 In this study, among the RBC indices, MCHC had the highest AUC, sensitivity, specificity, and Youden's index. Moreover, we found low MCHC level in patients with PD; this finding is consistent with previous findings.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…[4][5][6][7]18 In addition, MPV has poor diagnostic value in patients with generalized anxiety disorder. 8 In this study, among the RBC indices, MCHC had the highest AUC, sensitivity, specificity, and Youden's index. Moreover, we found low MCHC level in patients with PD; this finding is consistent with previous findings.…”
Section: Discussionmentioning
confidence: 49%
“…[4][5][6][7] Furthermore, Almis et al in their study including a small group of patients with generalized anxiety disorder reported that MPV is a poor biochemical marker, indicating the need to explore other diagnostic markers. 8 The simple inexpensive red blood cell (RBC) indices, such as RBC distribution width (RDW) and the RBC count, may have diagnostic and prognostic value in patients with PD. 4 Studies have reported that both the platelet and RBC indices are altered in patients with depression, anxiety, psychosis, PD, or schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…MPV has been found to be elevated in various mental disorders. The relationship between anxiety disorders, bipolar disorder, schizophrenia, major depression and increased platelet activity has been reported by several studies [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 91%
“…Other studies have focused on generalized anxiety disorder (GAD), a related disease characterized by a persistent and chronic anxiety state. In the first (retrospective) study specifically focusing on GAD patients, these showed higher MPV and lower Plt, but no significant differences in PDW and PCT, compared to healthy controls [ 173 ]. In partial concordance with these findings, GAD patients exhibited a higher MPV and Plt, as did MDD patients, in a study comparing depressive and anxiety disorder patients vs. healthy controls in a hospital setting [ 146 ].…”
Section: Mdd Comorbidities and Plateletsmentioning
confidence: 99%